On ordered pluralism - Queloz, M (Routledge, 2021)
This paper examines Miranda Fricker’s method of paradigm-based explanation and in particular its promise of yielding an ordered pluralism. Fricker’s starting point is a schism between two conceptions of forgiveness, Moral Justice Forgiveness and Gifted Forgiveness. In the light of a hypothesis about the basic point of forgiveness, she reveals the unity underlying the initially baffling plurality and brings order into it, presenting a paradigmatic form of forgiveness as explanatorily basic and other forms as derivative. The resulting picture, she claims, is an ‘explanatorily satisfying ordered pluralism.’ But what is this ordered pluralism and how does Fricker’s method deliver it? And to what extent can this strategy be generalised to other conceptual practices? By making explicit and critically examining the conception of ordered pluralism implicit in Fricker’s procedure, I assess the promise that her approach holds as a way of resolving stand-offs between warring conceptions of ideas or practices more widely. I argue that it holds great promise in this respect, but that if we are to avoid reproducing just the schismatic debates that the pluralism of paradigm-based explanation is supposed to overcome at the level of what is to be regarded as a paradigm case, we need to take seriously the thought that what counts as a paradigm is partly determined by our purposes in giving a paradigm-based explanation.